Iron-Binding and Anti-Fenton Properties of Novel Amino Acid-Derived Cyclic Imide Dioximes - Janez Mravljak; Žiga Jakopin (MDPI AG, 2019)
We present a novel route for the preparation of amino acid-derived cyclic imide dioxime derivatives. Readily accessible amino acids were conveniently converted to their corresponding cyclic imide dioximes in simple synthetic steps. The aim of this work was to describe and compare the iron-chelating and antioxidant properties of synthesized compounds in relation to their molecular structure, and in particular, which of those features are essential for iron(II)-chelating ability. The glutarimide dioxime moiety has been established as an iron(II)-binding motif and imparts potent anti-Fenton properties to the compounds. Compound 3 was shown to strongly suppress hydroxyl radical formation by preventing iron cycling via Fe-complexation. These findings provide insights into the structural requirements for achieving anti-Fenton activity and highlight the potential use of glutarimide dioximes as antioxidants.